Children's emotion understanding in relation to attachment to mother and father - Psychogiou, L; Nath, S; Kallitsoglou, A; Dimatis, K; Parry, E; Russell, A; Yilmaz, M; Kuyken, W; Moberly, N (John Wiley and Sons, Ltd., 2018)
Although attachment plays a key role in children's socio‐emotional development, little attention has been paid to the role of children's attachment to their father. This study examined whether insecure attachment to each parent was associated with reduced emotion understanding in children and whether children showed consistent attachments to their mother and father. We measured children's attachment to each parent using the Manchester Child Attachment Story Task and child emotion understanding using the Test of Emotion Comprehension (children's Mage = 5.64 years, SD = 0.84). The results indicated that insecure father–child attachment and insecure mother–child attachment were each associated with lower emotion understanding in children after controlling for parent's depressive symptoms and children's age. There was significant concordance of child attachment to mother and father. The findings provide support for convergence of children's attachment across parents and suggest that father–child attachment is an important factor to consider when examining children's emotion understanding.